The Effectiveness of the Traditional Game Tapo’ Pipit to Stimulate Language Development in Children Aged 5-6 Years at Primanda Kindergarten Untan - Wananda, Tasya; Halida, Halida; Ramadhani, Ariyani; Lukmannulhakim (Jurnal Pendidikan Anak, 2024)
The implementation of this research is to understand the productivity of the tape pipit game for children aged five to six years in class B1 of Kindergarten Primanda Untan. This research uses an experimental approach. The model used was ten children, with boys and girls five to five. The data collection methods are observation, documentation, and test sheets. The research instrument applies three indicators, namely, children listen to every word they hear, children can express and express their thoughts, and children can communicate orally. Through the observations made, researchers witnessed language development that was still not optimal in some children, researchers saw that language abilities in some children were still not optimal. Based on what is happening in the field, researchers are interested in using the traditional game Tapo’ Pipit to improve the language skills of children aged five to six years in class B1 at Primanda Untan Kindergarten. Based on the results obtained from this research, it indicate that there were differences before being given the traditional tapo’ pipit game and after being given the tapo’ pipit game. Where the average posttest result is higher than the average pretest result, namely the posttest is 47.8 and the pretest is 38.5. So it can be concluded that the Tapo’ Pipit game can stimulate the language development of children aged five to six years in class B1 Primanda Kindergarten Untan.